Integrating public health students into interprofessional education. Issue 3 (3rd May 2020) - Averill, Michelle M.; Dillon-Sumner, Laurel; Stergachis, Andy; Sconyers, Jeff; Summerside, Nicole; Brazg, Tracy; Errett, Nicole
ABSTRACT: Recognizing the public health professional are critical members of interprofessional teams, the Council on Education for Public Health (CEPH) recently added a required Masters of Public Health (MPH) student competency focused on interprofessional education (IPE). A student-centered approach to the design and evaluation of an emergency preparedness-focused curricular program to meet the interprofessional needs of MPH students was used to meet this expectation at the University of Washington. Curriculum design was informed by two 80-minute listening sessions with MPH students to better understand their current interprofessional educational experiences and needs, and how an emergency preparedness-focused two-hour Interprofessional Active Learning Series (iPALS) session could help them develop interprofessional competency. The resultant iPALS session was assessed with a short, paper-based questionnaire. We found MPH students have an interest in participating in IPE, and that all students who participated in the emergency preparedness-focused iPALS session reported significant increases in their interprofessional and disaster response abilities based on their pre- and post-session evaluations. Student-centered IPE curriculum focused on emergency preparedness can enhance the self-reported ability of students across the health sciences to perform on interprofessional teams while engaging in a topic that has relevance to MPH students.